Imaging in gynecological disease (12): clinical and ultrasound features of invasive and non‐invasive malignant serous ovarian tumors. (2nd November 2017) - Moro, F.; Baima Poma, C.; Zannoni, G. F.; Vidal Urbinati, A.; Pasciuto, T.; Ludovisi, M.; Moruzzi, M. C.; Carinelli, S.; Franchi, D.; Scambia, G.; Testa, A. C.
ABSTRACT: Objectives: To describe clinical and ultrasound features of different subclasses of malignant serous ovarian tumors according to the World Health Organization 2014 classification. Methods: Patients with a histological diagnosis of borderline tumor (BOT), non‐invasive and invasive low‐grade serous carcinoma (LGSC) and high‐grade serous carcinoma (HGSC), who had undergone preoperative ultrasound examination, were retrospectively identified from two ultrasound centers. The masses were described using the terms of the International Ovarian Tumor Analysis Group. Results: Sixty‐four (15.8%) women had a serous BOT, 11 (2.7%) a non‐invasive LGSC, 31 (7.6%) an invasive LGSC and 300 (73.9%) had a HGSC. The vast majority of BOTs (82.3%) and non‐invasive LGSCs (90.9%) were Stage I according to the International Federation of Gynecology and Obstetrics (FIGO) classification scheme, whereas most invasive LGSCs (74.2%) and HGSCs (74.0%) were FIGO Stage III. On ultrasound examination, most borderline lesions were described as unilocular‐solid (54.7%) or as multilocular‐solid (29.7%) cysts. Papillary projections were present in 52 (81.3%) BOTs. Most non‐invasive LGSCs (63.6%) were multilocular‐solid cysts and 81.8% had papillary projections. Invasive LGSCs were multilocular‐solid cysts in 54.8% of cases, and papillary projections were present in 32.3% of lesions. HGSCs were multilocular‐solid (32.7%) or solid (64.0%) masses, with papillary projections in only 7% of cases. Conclusions: Papillary projections were the most typical ultrasound feature of non‐invasive (borderline and low‐grade) malignant serous tumors, while the presence of solid components but few, if any, papillations was the most representative feature of invasive (low‐grade and high‐grade) serous tumors. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.